(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The main purpose of this study is to demonstrate how to use the Binomial-Option Pricing Model (BOPM) to determine the premium of an option by constructing a risk-free arbitrage portfolio consisting of a position in stock and option. Financial derivatives are widely used in a variety of financial markets to manage various risks efficiently and economically. This paper will mainly focus on the pricing and valuation of options by using the Binomial Option Pricing Model (BOPM) to determine the theoretical fair value of options for one or multiple periods. In addition, this study seeks to develop a hedging portfolio consisting of a specific mix of a number of stocks and options for a sample of Jordanian banks listed in Amman Stock Exchange during the period between 2020 and 2021. Appropriate methodologies have been followed to determine the fair value of the option price and to create a hedge portfolio that produces a risk-free return. This study shows that the BOPM model gives acceptable results when applied to the financial sector in the ASE; moreover, it shows that designing a hedged portfolio can reduce risks compared to unhedged portfolios to a significant level. This paper gives a great benefit to portfolio managers in identifying risk management techniques by creating a risk-free hedging portfolio so that the value of the option can be deduced from other variables that can be determined, as well as helping shareholders to reduce risks through the use of option contracts as investment tools. On the other hand, this study points to the need of having sufficient knowledge regarding the fundamentals to understand the nature of this type of derivatives, and how they can be used to avoid risks through an appropriate protective strategy and to achieve reasonable returns.